Natural Products from Marine Invertebrates and Microbes as Modulators of Antitumor Targets - Newman, D. J.; Cragg, G. M. (Current Drug Targets, 2006)
Over the last twenty-five to thirty years, exploration of the marine fauna and microbial flora has progressed from a random search by natural product chemists who liked to dive and wished to combine their hobby with their profession, to fully integrated programs of systemic investigation of the chemical agents elaborated by marine organisms of all phyla (as presumably defensive agents against predators) for their potential as leads to human-use drug candidates where the putative mechanisms have been identified as modulation of, and/or interaction with, potential molecular targets, rather than just exhibiting general cytotoxicity. This review is not exhaustive but is meant to cover the highlights of such agents and is arranged on a (nominal) target basis rather than by organism or chemical class.
Keywords: Marine natural products